Caminante, No Hay Camino, Se Hace Camino al Andar: On a Creative Research Project in Urban Planning - Laurent Matthey; Simon Gaberell; Alice Chenais; Jade Rudler; Aude Seigne; Anne-Sophie Subilia; Daniel Vuataz; Matthieu Ruf (Social Inclusion, 2023)
This article looks back at a creative research project conducted in Geneva, Switzerland, which, by experimenting between art and science, sought to understand how citizen narratives can participate in the making of an urban plan. The approach presented here brought together geographers, architects, and novelists. Citizen narratives produced at writing workshops imagined the city of the future in ways that significantly contrasted with visions gathered from events organised by public authorities. These narratives were taken up by the novelists, who helped produce a piece of fiction containing the power to reveal the qualities of the present. This piece has since become a novel. By discovering what their future city could be, participants in this project were led to identify the places that should be preserved. Their narratives thus helped identify an ordinary heritage that could be included in an urban planning document. This reflective look at a project that gradually took shape could be useful to anyone wishing to conduct creative research in urban planning, particularly from the perspective of a more inclusive city.